Low glycemic index therapy in children with sub-acute sclerosing panencephalitis (SSPE): an experience from a measles-endemic country - Ibrahim, Shahnaz H.; Farooq, Hira (Frontiers in Nutrition, 2023)
Introduction: Sub-acute Sclerosing Panencephalitis (SSPE) is a chronic, progressive neurodegenerative disorder, commonly seen in measles-endemic countries leading to progressive neuronal loss and death. Currently, there is no proven cure for this devastating disease. We started a Low Glycemic Index Therapy (LGIT) in children with SSPE using the same principle as per its role in intractable epilepsy.Methodology: Low glycemic index diet was started in children with a confirmed diagnosis of SSPE based on the Dyken's criteria. All children were then classified according to disease progression into IV stages. The response to diet was evaluated by improvement in their myoclonic jerks, motor activities and change in their stage of disease.Results: Twelve children were enrolled. The mean age was 6.65 years (range 3.3 -10 years), with a male to female ratio of 2:1. Five children were at stage IV, five were at stage III and two were at stage II at the start of the diet. Nine (75%) children improved in their stage of illness. Of three children who were at stage IV at initiation of diet, one improved to stage II and two to stage III. Four children at stage III reverted to stage II. Two children initiated at stage II went into total remission. Seven (58.3%) children showed a > 50% reduction in myoclonic jerks with three (25%) having 100% reduction. Three (25%) children died due to pneumonia.LGIT may play an effective role in the management of SSPE and gives hope to families having children with this potentially life-threatening disease.